La racialisation des espaces urbains à La Nouvelle-Orléans post-Katrina : étude des représentations fictionnelles dans la série télévisée Treme - Catherine DESSINGES; Dominique GENDRIN (E-REA)
This paper investigates the manner in which David Simon and Eric Overmyer’s HBO TV series Treme (2010-2013) represents the process of racialization of urban spaces. First aired on April 11, 2010 as a pilote episode, Treme follows the difficult return of the residents of New Orleans after Katrina, and their struggle to recover their homes, their lives, and their culture. Treated as a drama by its producers, the series does take a documentary approach by giving a realistic representation of the citizens’ rebuilding process of New Orleans after Katrina. Through key dialogues and scenes, this article proposes to analyze the fictional representations of the racialization of urban spaces (streets, the French Quarter, black neighborhoods, housing projects...) presented in the series as identity markers and spaces of racial discrimination, by underlying the manner in which the series articulates the concepts of place, race, and space. It demonstrates how the series' creators reveal a type of territorialism grounded in racialized practices that we have labeled « urban restrictions », « urban visibility/invisibility » and « urban redevelopment ».